Leader-member exchange differentiation and team creativity. Issue 7 (7th September 2015) - Zhao, Hongdan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the effect of leader-member exchange (LMX) differentiation on team creativity by developing a moderated mediation model. The model focuses on the mediating role of relationship conflict in linking LMX differentiation with team creativity and the moderating role of team-member exchange (TMX) median in influencing the mediation. Design/methodology/approach – The authors tested the model with a time-lagged field survey data from 358 employees and 98 supervisors belonging to 98 teams in a large diversified company with more than 15, 000 employees, based in Shanghai, Southeastern China. In the first stage (T1), employees assessed LMX, TMX, relationship conflict, and control variables. In the second stage (T2), the leaders were asked to report team creativity. Findings – Results indicated that the relationship between LMX differentiation and team creativity was mediated by relationship conflict. Moderated mediation analyses further revealed that relationship conflict mediated the relationship between LMX differentiation and team creativity for only those teams with low-TMX median. Research limitations/implications – Testing the moderated mediation model helps to advance our theoretical understanding of the intervening processes that underlie the effect of LMX differentiation on team creativity. The findings may also help Chinese managers to inform the importance of helping subordinates better adapt to LMX differentiation, reducing relationship conflict, and constructing high-quality TMX relationships within groups, in order to promote team creativity. Originality/value – This empirical study provides preliminary evidence of the mediating role of relationship conflict in the negative relationship between LMX differentiation and team creativity. The moderated mediation model also extends the existing finding by showing that not only the quality of social exchange relationships with a supervisor (i.e. LMX) but also with team members (i.e. TMX), can moderate the impact of LMX differentiation on team outcomes.